TELEMEDICINE USE IN HEALTH FACILITY DURING COVID-19 PANDEMIC: LITERATURE REVIEW - Widya Hapsari Murima; Ahmad Rido'i Yuda Prayogi; Aisyah Putri Rahvy; Nuranisah Djunaedi; Inge Dhamanti (Indonesian Journal of Health Administration, 2022)
Background: The policy of imposing restrictions on community activities during the Covid-19 pandemic is a challenge to the accessibility of health services. Therefore, we need the best solution for safe access to health services. Aims: This study aims to analyze telemedicine use in health facilities during the Covid-19 pandemic by looking at comparisons and similarities in use and reviewing the inhibiting and supporting factors for the success of telemedicine. Methods: The research method is a literature review that was obtained through the Scopus database and published in 2020-2021 in English. Cleaning of articles was carried out with the inclusion and exclusion criteria so that seven articles were reviewed. Results: The lack of multidisciplinary use, healthcare practitioners' inability to connect with patients, under-integrated systems, and lack of technological knowledge and capacity all hinder telemedicine adoption. Positive patient feedback, a well-supported telemedicine service system, and partnerships with specialists all help make telemedicine more effective. Conclusion: During a pandemic, the use of telemedicine in healthcare settings is extremely beneficial for healthcare providers and patients during healthcare consultations, and there are supporting aspects such as WHO recognition and simplicity of operation. However, obstacles remain, such as a lack of specialized knowledge and multidisciplinary technology.